Genetic Distance and Conservation Status of Stingray Species at TPI Tasik Agung Rembang, Central Java based on the Mitochondrial Cytochrome Oxidase I Gene - Ning Setiati; Sarah; Partaya; Priyantini Widyaningrum; Dyah Rini Indriyanti; Endah Peniati (Science & Technology Asia, 2023)
Genetic distance and conservation status of stingray species at TPI Tasik Agung Rembang, Central Java utilizes the mitochondrial cytochrome oxidase I (COI) gene. The objective of this research is to examine the genetic distance and conservation status of five stingray species discovered in TPI (Fish Auction) Tasik Agung: Himantura uarnacoides, Himantura walga, Himantura gerrardi, Rhinobatos penggali, and Brevitrygon heterura. Eventually, the acquired data can be applied as important basic information to preserve genetic diversity in stingray populations. The DNA barcode approach was performed on the COI gene using the polymerase chain reaction (PCR) technique. The sequences obtained were edited in the Basic Local Alignment Search Tool (BLAST) program before being analyzed in MEGA 10 software for phylogenetic tree reconstruction and genetic distance measurement. The genetic distance between the most closely related species was 0.002 (Dasyatis zugei and Telatrygon zugei), and the most significant genetic distance was 0.231 (Rhinobatos penggali and Brevitrygon heterura with Himantura walga). The IUCN conservation status of stingrays observed during the study revealed four species in the vulnerable category (VU) and one species in the near threatened (NT) category.